Online Gaming: A Virtual Experiment in the Dark Side of Human Nature. - GLYNN, JOHN (Skeptic, 2019)
The article examines the financial motivations and techniques behind cheating in online video games. It focuses on massively-multiplayer online role playing games (MMORPGs) and discusses how players' achievements, accomplishments, and characters can be stolen by hackers through scams that then convert the stolen items for real-world value.